2019
DOI: 10.3928/01477447-20190624-08
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Morel-Lavallée Lesion of the Back With Transcutaneous Transmyofascial Bolstered Progressive Tension Suturing

Abstract: The authors describe their experience in successfully treating an isolated Morel-Lavallée lesion of the lumbar spine after delayed presentation. In addition to thorough irrigation, debridement, and pseudo-capsulectomy, surgical management included transcutaneous transmyofascial bolstering with a progressive tension suturing technique to close the cavity over drains in a “quilting” fashion. This was followed by 6 days of incisional wound vacuum treatment and 13 days of drainage through 2 Jackson-Pratt drains. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The traditional method is irrigation and drainage through one or more limited small incisions 28,51 . It has also been reported that progressive tension sutures, quilting, fibrin sealant, and low suction drains can successfully achieve the above goal 14,17,18,49,52–57 . Kalaria et al successfully applied liposuction cannulas to destroy the cavity of the lesion 58 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional method is irrigation and drainage through one or more limited small incisions 28,51 . It has also been reported that progressive tension sutures, quilting, fibrin sealant, and low suction drains can successfully achieve the above goal 14,17,18,49,52–57 . Kalaria et al successfully applied liposuction cannulas to destroy the cavity of the lesion 58 .…”
Section: Methodsmentioning
confidence: 99%
“… 28 , 51 It has also been reported that progressive tension sutures, quilting, fibrin sealant, and low suction drains can successfully achieve the above goal. 14 , 17 , 18 , 49 , 52 , 53 , 54 , 55 , 56 , 57 Kalaria et al successfully applied liposuction cannulas to destroy the cavity of the lesion. 58 Li et al successfully applied a minimally invasive incision in combination with loop drainage technique to treat Morel‐Lavallée lesion of the lower extremity and named this technique as nose ring drainage technique.…”
Section: Methodsmentioning
confidence: 99%